Impact of External Environmental Factors on Construction Firms' Performance, Mediated By Institutional Pressures - Hassan Fehan; Osaro Aigbogun (Civil Engineering Journal, 2022)
While the mainstream of construction management research has paid attention to the causes of poor performance in construction projects, there is a dearth of empirical research that considers the influence of external environment and institutional pressures in the debate. The objective of this research was to examine the impact of external environmental factors and institutional pressures on the performance outcomes of construction firms. The role of institutional pressures as a mediator in that relationship was also evaluated. Using a self-administered questionnaire, primary data was collected from 250 executives working in construction firms. This was then analysed using partial least squares structural equation modelling. The results demonstrated that both external environmental factors and institutional pressures have an impact on the performance of construction firms. In light of the institutional theory, the findings addressed a genuine research gap, as institutional pressures were discovered to mediate the relationship between external environmental factors and construction firm performance outcomes. This study contributes to the current debate about the causes of poor performance in construction firms by assisting managers in recognizing the impact of the aforementioned factors on a firm's performance. Doi: 10.28991/CEJ-2022-08-05-09 Full Text: PDF